Hyphoderma paramacaronesicum sp. nov. (Meruliaceae, Polyporales, Basidiomycota), a cryptic lineage to H. macaronesicum - Martín, M.P. (Fungal Syst Evol, 2018)
This article re-evaluates the taxonomy of Hyphoderma macaronesicum based on various strategies, including the cohesion species recognition method through haplotype networks, multilocus genetic analyses using the genealogical concordance phylogenetic concept, as well as species tree reconstruction. The following loci were examined: the internal transcribed spacers of nuclear ribosomal DNA (ITS nrDNA), the intergenic spacers of nuclear ribosomal DNA (IGS nrDNA), two fragments of the protein-coding RNA polymerase II subunit 2 (RPB2), and two fragments of the translation elongation factor 1-α (EF1-α). Our results indicate that the name H. macaronesicum includes at least two separate species, one of which is newly described as Hyphoderma paramacaronesicum. The two species are readily distinguished based on the various loci analysed, namely ITS, IGS, RPB2 and EF1-α.